Short chain nitrocompounds as a treatment of layer hen manure and litter; effects on in vitro survivability of Salmonella, generic E. coli and nitrogen metabolism. Issue 1 (2nd January 2017) - Ruiz-Barrera, Oscar; Anderson, Robin C.; Hume, Michael E.; Corrales-Millan, Jonatan; Castillo-Castillo, Yamicela; Corral-Luna, Agustin; Guevara-Valdez, Jose Luis; Salinas-Chavira, Jaime; Rodriguez-Muela, Carlos; Arzola-Alvarez, Claudio
ABSTRACT: The current study was conducted to assess the bactericidal effectiveness of several nitrocompounds against pathogens in layer hen manure and litter. Evidence from an initial study indicated that treatment of layer hen manure with 12 mM nitroethane decreased populations of generic E. coli and total coliforms by 0.7 and 2.2 log10 colony forming units (CFU) g −1, respectively, after 24 h aerobic incubation at ambient temperature when compared to untreated populations. Salmonella concentrations were unaffected by nitroethane in this study. In a follow-up experiment, treatment of 6-month-old layer hen litter (mixed with 0.4 mL water g −1 ) with 44 mM 2-nitroethanol, 2-nitropropanol or ethyl nitroacetate decreased an inoculated Salmonella typhimurium strain from its initial concentration (3 log10 CFU g −1 ) by 0.7 to 1.7 log10 CFU g −1 after 6 h incubation at 37°C in covered containers. After 24 h incubation, populations of the inoculated S. Typhmiurium in litter treated with 44 mM 2-nitroethanol, 2-nitropropanol, ethyl nitroacetate or nitroethane were decreased more than 3.2 log10 CFU g −1 compared to populations in untreated control litter. Treatment of litter with 44 mM 2-nitroethanol, 2-nitropropanol, ethyl nitroacetate decreased rates of ammonia accumulation more than 70% compared to untreated controls (0.167 µmol mL −1 h −1 ) and loses of uric acid (< 1 µmol mL −1 ) were observed only in litter treated with 44 mM 2-nitropropanol, indicating that some of these nitrocompounds may help prevent loss of nitrogen in treated litter. Results warrant further research to determine if these nitrocompounds can be developed into an environmentally sustainable and safe strategy to eliminate pathogens from poultry litter, while preserving its nitrogen content as a nutritionally valuable crude protein source for ruminants.